Before and after implementation of group antenatal care in Rwanda: a qualitative study of women's experiences - Angele Musabyimana; Tiffany Lundeen; Elizabeth Butrick; Felix Sayinzoga; Bernard Ngabo Rwabufigiri; Dilys Walker; Sabine F. Musange (BMC, 2019)
Abstract Background The Preterm Birth Initiative-Rwanda is conducting a 36-cluster randomized controlled trial of group antenatal and postnatal care. In the context of this trial, we collected qualitative data before and after implementation. The purpose was two-fold. First, to inform the design of the group care program before implementation and second, to document women's experiences of group care at the mid-point of the trial to make ongoing programmatic adjustments and improvements. Methods We completed 8 focus group discussions among women of reproductive age before group care implementation and 6 focus group discussions among women who participated in group antenatal care and/or postnatal care at 18 health centers that introduced the model, approximately 9 months after implementation. Results Before implementation, focus group participants reported both enthusiasm for the potential for support and insight from a group of peers and concern about the risk of sharing private information with peers who may judge, mock, or gossip. After implementation, group care participants reported benefits including increased knowledge, peer support, and more satisfying relationships with providers. When asked about barriers to group care participation, none of them cited concern about privacy but instead cited lack of financial resources, lack of cooperation from a male partner, and long distances to the health center. Finally, women stated that the group care experience would be improved if all participants and providers arrived on time and remained focused on the group care visit throughout. Discussion These results are consistent with other published reports of women's perceptions of group antenatal care, especially increased pregnancy- and parenting-related knowledge, peer support, and improved relationships with health care providers. Some results were unexpected, especially the consequences of staff allocation patterns that resulted in providers arriving late for group visits or having to leave during group visits to attend to other facility services, which diminished women's experiences of care. Conclusion Group antenatal and postnatal care provide compelling benefits to women and families. If the model requires the addition of human resources at the health center, intensive reminder communications, and large-scale community outreach to benefit the largest number of pregnant and postnatal mothers, those additional resources required must be factored into any future decision to scale a group care model. Trial registration This trial is registered at clinicaltrials.gov as NCT03154177.